1981
DOI: 10.3171/jns.1981.54.2.0228
|View full text |Cite
|
Sign up to set email alerts
|

Incidental pituitary adenomas

Abstract: Pituitary glands from 500 consecutive autopsies were reviewed and the findings correlated with clinical symptomatology. Occult pituitary adenomas were identified in 42 pituitary glands (8.5%). In only one case was a pituitary lesion clinically questioned, but specific hypophyseal function studies were not performed. These tumors occurred most frequently in the sixth and seventh decade of life, without obvious sex predominance. Of these patients, 48% were obese, 57% were hypertensive, and diabetes mellitus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
2
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(46 citation statements)
references
References 3 publications
1
40
2
3
Order By: Relevance
“…However, even today, pituitary adenomas are a common incidental finding at the time of autopsy. 3,4 With wider application of computed tomography (CT) and magnetic resonance imaging (MRI), pituitary masses will be detected incidentally during patients' lifetimes in increasing frequency. The diagnostic and therapeutic approach to patients with "incidentalomas" of the pituitary gland has not yet been established.…”
mentioning
confidence: 99%
“…However, even today, pituitary adenomas are a common incidental finding at the time of autopsy. 3,4 With wider application of computed tomography (CT) and magnetic resonance imaging (MRI), pituitary masses will be detected incidentally during patients' lifetimes in increasing frequency. The diagnostic and therapeutic approach to patients with "incidentalomas" of the pituitary gland has not yet been established.…”
mentioning
confidence: 99%
“…In corroboration of these indirect investigations of pituitary anatomy, pituitary microadenomas have been observed in up to 20% of sequential autopsy analyses of the hypophysis (2,3). Although several prospective studies have indicated that most pituitary microadenomas detected incidentally in imaging studies have an extremely benign course (4,5), it is also quite obvious that pituitary macroadenomas must undergo an apparent 'microadenomatous phase'.…”
Section: Introductionmentioning
confidence: 73%
“…Dilution of serum samples must be specifically requested if suspicion of the hook effect is high enough. 8,13,14 Of the major anterior pituitary hormonal axes, the two that typically require the most attention with regard to hormonal replacement prior to any intervention are the cortisol and thyroid axes. Medical replacement of hypofunctioning cortisol or thyroid axes should be implemented prior to any operation, typically in collaboration with an endocrinologist.…”
Section: Methodsmentioning
confidence: 99%